2016
DOI: 10.1111/jbi.12774
|View full text |Cite
|
Sign up to set email alerts
|

Environmental correlates of floristic regions and plant turnover in the Atlantic Forest hotspot

Abstract: Aim Using a comprehensive floristic database (2616 species, 36,004 occurrence records from 128 unique localities), we model species turnover along the central region of the Atlantic Forest hotspot to (1) test whether local rivers, particularly the Rio Doce, are associated with marked biogeographical breaks, and (2) investigate how regional compositional changes correlate with geo-climatic variables.Location The central region of the Atlantic Forest in eastern Brazil (12°-22°S latitude). MethodsWe combine occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 64 publications
2
10
1
1
Order By: Relevance
“…In contrast to that has been found for a variety of tropical vegetation types and floristic assemblages (e.g. Cantidio & Souza, 2019;Castro-Insua et al, 2018;Linder et al, 2012;Marques et al, 2020;Saiter et al, 2016;Tuomisto et al, 2019), we found rather smooth borders between subregions. This is attributable to the absence of extensive mountain ranges or steep climatic gradients in most of the Amazon extension, as well as to the historical stability of the tropical forest biome in the basin (Costa et al, 2017), which may have allowed for extensive species dispersal.…”
Section: Regional Patternscontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to that has been found for a variety of tropical vegetation types and floristic assemblages (e.g. Cantidio & Souza, 2019;Castro-Insua et al, 2018;Linder et al, 2012;Marques et al, 2020;Saiter et al, 2016;Tuomisto et al, 2019), we found rather smooth borders between subregions. This is attributable to the absence of extensive mountain ranges or steep climatic gradients in most of the Amazon extension, as well as to the historical stability of the tropical forest biome in the basin (Costa et al, 2017), which may have allowed for extensive species dispersal.…”
Section: Regional Patternscontrasting
confidence: 99%
“…Our results supported the recently raised point that vegetation maps based on physiognomic variation should not be used as proxies to plant diversity subregions, due to the marked mismatch between vegetation types and biodiversity subregions (Cantidio & Souza, 2019;Saiter et al, 2016;Silva & Souza, 2018a). For example, broadleaved evergreen pluvial forests cover most of the Amazon forest domain ( Figure S1), and yet we found different compositional subregions within this single physiognomy.…”
Section: Comparison With Previous Regionalization Attemptssupporting
confidence: 89%
See 2 more Smart Citations
“…However, when decoupling of FD into separate functional components, each showed varying relationships between landscape associations and different ecological characteristics for different assemblages (Cisneros et al, ). In the AF, precipitation and temperature variables have been shown to play important roles in structuring of invertebrate (Brown & Freitas, ), mammal (de la Sancha et al, ; Stevens, ), fish (Vilella, Becker, Hartz, & Barbieri, ), and plant (Leitman, Amorim, Sansevero, & Forzza, ; Zamborlini Saiter, Brown, Thomas, Oliveira‐Filho, & Carnaval, ) assemblages, communities, and metacommunities.…”
Section: Discussionmentioning
confidence: 99%